Endoscopic balloon dilation for the prevention of severe strictures caused by acute esophageal necrosis. Issue 1 (1st September 2021) - Jinushi, Ryuhei; Ishii, Naoki; Yano, Takahiko; Imamura, Noriatsu; Maekawa, Hisato; Kamachi, Kenichi
Abstract: A 58‐year‐old man who had the history of alcohol dependence was referred to our emergency center due to severe nausea, vomiting, and subsequent onset of chest and back pain. Esophagogastroduodenoscopy (EGD) showed black‐appearing esophagus mucosa extending from the cervical esophagus to the esophagogastric junction with clear margins, a condition typically referred to as a black esophagus. Alcohol abuse was considered an important factor associated with acute esophageal necrosis in this patient. After admission, he received fluid resuscitation and proton‐pump inhibitors, with restriction of oral intake and treatment of alcohol dependence. Follow‐up EGDs and endoscopic balloon dilation were performed for the management of esophageal narrowing before the development of severe strictures. Strictures were successfully treated endoscopically without complications such as perforation.